Proceedings of the Seventh International Conference on Languages and Arts (ICLA 2018) 2019
DOI: 10.2991/icla-18.2019.48
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Youtube as A Teaching Media on the Students’ Listening Skill (The Case of 2nd Semester Students of English Education Study Program of IKIP-PGRI Pontianak)

Abstract: The objectives of the research are: (1) to identify whether using youtube are more effective than using audio in teaching listening skill; (2)To identify whether there is an interaction between Youtube and Audio on listening skill. The research was conducted at IKIP-PGRI Pontianak. The population of the research was the second semester students in English Study Program. The sample of the research was A Morning class who were taught by using Youtube and the B Morning class who were taught by using audio. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It was suggested that students performed better on the listening comprehension exam after receiving instruction using a mix of computer-assisted learning techniques and traditional pedagogy than they did before receiving the treatment. Rizkan et al (2019) also state that Youtube is more effective than audio in improving students' listening abilities in IKIP PGRI-Pontianak high schools. So, it is suggested that lecturers utilize YouTube as a medium or assist their students' media in listening to the instruction.…”
Section: Youtube Videos On Efl College Students'mentioning
confidence: 90%
See 1 more Smart Citation
“…It was suggested that students performed better on the listening comprehension exam after receiving instruction using a mix of computer-assisted learning techniques and traditional pedagogy than they did before receiving the treatment. Rizkan et al (2019) also state that Youtube is more effective than audio in improving students' listening abilities in IKIP PGRI-Pontianak high schools. So, it is suggested that lecturers utilize YouTube as a medium or assist their students' media in listening to the instruction.…”
Section: Youtube Videos On Efl College Students'mentioning
confidence: 90%
“…Some related studies show that YouTube can be used for teaching, practicing, or improving listening to English, for example: Listening Skill" (Rizkan et al, 2019) their students' media in listening to the teaching.…”
Section: Youtubementioning
confidence: 99%
“…Listening takes a significant role which needs 40-50% part in a communication rather than the other language skills. Listening refers to an ability in conveying and comprehending what others are saying (Rizkan et al, 2020). Thus, it simply stated that listening refers to an active process which involves ability in conveying and understanding the words or massages in order to build communication.…”
Section: Introductionmentioning
confidence: 99%
“…However, teachers should consider a good video and appropriate with the learning materials and objectives (Obagah & Brisibe, 2017;Yacoob & Saad, 2020). While most of the aforementioned of previous studies focused on investigating the effect of video on students listening skill in a university students and junior high school students, some of them tend to use different method of data analysis, setting, and topics of the learning materials (Aboudahr & Farag, 2020;Rahmadani, 2018;Rizkan et al, 2020;Sutrisno, 2020). However, from the review of previous studies, it can prove that the use of video as learning tool or materials give a significant impact on listening comprehension skill.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, YouTube, as an online video sharing platform, can display a variety of activities related to the teaching and learning process (Hwang, 2009) Rorimpandey ( 2019) found out that using YouTube video for listening comprehension in the Basic Listening course resulted in a higher listening comprehension score than using traditional media. In another report, Rizkan et al (2019) concluded that YouTube was more successful than audio alone in improving students' listening skills. The tasks are more complex, and the learning environment is not monotonous.…”
Section: Introductionmentioning
confidence: 99%